Learn more about

Refine search

Results (displaying matches 1-50 of 5140) Next

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
336.a.172032.1 336.a \(y^2 + (x^3 + x)y = -x^6 + 15x^4 - 75x^2 - 56\) $G_{3,3}$ 0
644.a.2576.1 644.a \(y^2 + (x^2 + x)y = -5x^6 + 11x^5 - 20x^4 + 20x^3 - 20x^2 + 11x - 5\) $G_{3,3}$ 0
672.a.172032.1 672.a \(y^2 + (x^3 + x)y = -x^6 - 16x^4 - 75x^2 + 56\) $G_{3,3}$ 0
676.b.17576.1 676.b \(y^2 + (x^2 + x)y = -x^6 + 3x^5 - 6x^4 + 6x^3 - 6x^2 + 3x - 1\) $E_1$ 0
708.a.181248.1 708.a \(y^2 + (x^3 + 1)y = -x^6 - 4x^5 + 9x^4 + 48x^3 - 41x^2 - 98x - 36\) $\mathrm{USp}(4)$ 0
784.b.25088.1 784.b \(y^2 + (x^2 + 1)y = -x^6 - 3x^5 + 7x^4 + 2x^3 - 49x^2 + 41x - 9\) $G_{3,3}$ 0
784.b.76832.1 784.b \(y^2 + (x + 1)y = -x^6 + 4x^5 - 4x^4 - 2x^3 + 10x - 9\) $G_{3,3}$ 0
800.a.8000.1 800.a \(y^2 + (x^3 + x^2 + x + 1)y = -x^6 + 2x^4 + 4x^3 + 2x^2 - 1\) $G_{3,3}$ 0
816.b.52224.1 816.b \(y^2 + (x^3 + x)y = -x^6 - 12x^4 - 27x^2 - 17\) $G_{3,3}$ 0
847.d.847.1 847.d \(y^2 + (x^3 + x^2 + x + 1)y = -12x^6 - 15x^5 + 9x^4 + 31x^3 + 9x^2 - 15x - 12\) $G_{3,3}$ 0
847.d.456533.1 847.d \(y^2 + y = -x^6 - 9x^5 - 22x^4 + 3x^3 + 37x^2 - 24x + 4\) $G_{3,3}$ 0
936.a.1872.1 936.a \(y^2 + (x^3 + x)y = -x^6 - 9x^4 - 32x^2 - 39\) $G_{3,3}$ 0
961.a.961.1 961.a \(y^2 + (x^3 + x + 1)y = -x^6 - x^5 - 7x^4 + 74x^3 - 145x^2 + 99x - 33\) $G_{3,3}$ 0
961.a.961.2 961.a \(y^2 + (x^3 + x + 1)y = -x^6 + 2x^5 - 8x^4 + 12x^3 - 18x^2 + 12x - 7\) $G_{3,3}$ 0
980.a.878080.1 980.a \(y^2 + (x^3 + 1)y = -x^6 + x^5 - 4x^4 + 2x^3 - 4x^2 + x - 1\) $G_{3,3}$ 0
1050.a.131250.1 1050.a \(y^2 + (x^2 + x)y = 3x^6 + 8x^5 + 15x^4 + 17x^3 + 15x^2 + 8x + 3\) $G_{3,3}$ 0
1083.b.87723.1 1083.b \(y^2 + y = -x^6 - 3x^5 - 8x^4 - 11x^3 - 14x^2 - 9x - 6\) $G_{3,3}$ 0
1083.b.390963.1 1083.b \(y^2 + y = -x^6 + 3x^5 - 50x^4 + 95x^3 - 14x^2 - 33x - 6\) $G_{3,3}$ 0
1104.b.141312.1 1104.b \(y^2 + (x^3 + x)y = -x^6 - 3x^4 + 29x^2 - 46\) $G_{3,3}$ 0
1170.a.10530.1 1170.a \(y^2 + (x^2 + x)y = 15x^6 + 28x^5 + 62x^4 + 59x^3 + 62x^2 + 28x + 15\) $G_{3,3}$ 0
1253.a.1253.1 1253.a \(y^2 + (x^3 + x^2 + 1)y = -x^6 + 2x^5 - 33x^3 + 43x^2 + 15x - 330\) $\mathrm{USp}(4)$ 0
1269.b.102789.1 1269.b \(y^2 + (x^3 + x)y = -2x^6 - x^5 - 21x^4 - 8x^3 - 80x^2 - 16x - 103\) $\mathrm{USp}(4)$ 0
1344.a.4032.1 1344.a \(y^2 + xy = -x^6 - 12x^4 - 48x^2 - 63\) $N(G_{1,3})$ 0
1460.a.5840.1 1460.a \(y^2 + (x^3 + x)y = x^6 + 14x^4 + 56x^2 + 73\) $G_{3,3}$ 0
1470.a.2940.1 1470.a \(y^2 + (x^2 + x)y = -x^6 + 2x^5 - 5x^4 + 4x^3 - 5x^2 + 2x - 1\) $G_{3,3}$ 0
1560.a.199680.1 1560.a \(y^2 + x^2y = 39x^6 - 149x^4 + 189x^2 - 80\) $G_{3,3}$ 0
1564.a.50048.1 1564.a \(y^2 + (x^3 + 1)y = -x^6 + 7x^5 + 8x^4 + 17x^3 + 8x^2 + 7x - 1\) $G_{3,3}$ 0
1680.a.16800.1 1680.a \(y^2 + (x^3 + x)y = -x^6 - 18x^4 - 136x^2 - 350\) $G_{3,3}$ 0
1795.a.224375.1 1795.a \(y^2 + (x^3 + x^2 + x)y = -x^6 - 8x^4 + 3x^3 - 23x^2 + 6x - 23\) $\mathrm{USp}(4)$ 0
1870.a.226270.1 1870.a \(y^2 + (x + 1)y = -2x^6 + x^5 - x^4 + 9x^3 - 2x^2 + 2x - 9\) $\mathrm{USp}(4)$ 0
1920.a.368640.1 1920.a \(y^2 + (x^3 + x^2 + x + 1)y = 5x^6 + 6x^5 + 17x^4 + 12x^3 + 17x^2 + 6x + 5\) $G_{3,3}$ 0
1923.a.1923.1 1923.a \(y^2 + (x^3 + x + 1)y = -x^6 + x^5 - 3x^4 + 2x^3 - 3x^2 + x - 1\) $\mathrm{USp}(4)$ 0
1988.a.3976.1 1988.a \(y^2 + (x^2 + x)y = 6x^6 + 16x^5 + 31x^4 + 35x^3 + 31x^2 + 16x + 6\) $G_{3,3}$ 0
2016.a.4032.1 2016.a \(y^2 + y = -2x^6 - 6x^5 - 10x^4 - 10x^3 - 7x^2 - 3x - 1\) $G_{3,3}$ 0
2058.a.2058.1 2058.a \(y^2 + (x^3 + 1)y = 5x^6 - 4x^5 - 5x^4 + 14x^3 - 5x^2 - 4x + 5\) $N(G_{1,3})$ 0
2058.a.16464.1 2058.a \(y^2 + (x^3 + 1)y = -3x^6 + 5x^5 - 11x^4 + 10x^3 - 11x^2 + 5x - 3\) $N(G_{1,3})$ 0
2178.a.13068.1 2178.a \(y^2 + (x^3 + 1)y = -x^6 - x^4 - x^2 - 1\) $G_{3,3}$ 0
2178.b.287496.1 2178.b \(y^2 + (x^2 + x)y = -x^6 - 2x^5 + 3x^4 - 8x^2 + 9x - 3\) $G_{3,3}$ 0
2208.a.141312.1 2208.a \(y^2 + (x^3 + x)y = -x^6 + 2x^4 + 29x^2 + 46\) $G_{3,3}$ 0
2280.a.4560.1 2280.a \(y^2 + (x^3 + x)y = x^6 + 13x^4 + 48x^2 + 57\) $G_{3,3}$ 0
2304.b.147456.1 2304.b \(y^2 = -x^6 - 2x^4 - 2x^2 - 1\) $E_1$ 0
2312.c.591872.1 2312.c \(y^2 + xy = -32x^6 - 31x^4 - 10x^2 - 1\) $G_{3,3}$ 0
2380.a.33320.1 2380.a \(y^2 + (x^2 + x)y = -14x^6 + 26x^5 - 56x^4 + 53x^3 - 56x^2 + 26x - 14\) $G_{3,3}$ 0
2484.a.9936.1 2484.a \(y^2 + (x^3 + x)y = -x^6 - 8x^4 - 24x^2 - 23\) $N(G_{1,3})$ 0
2500.a.400000.1 2500.a \(y^2 + (x^3 + 1)y = -2x^6 - 2x^5 + 2x^3 - 2x - 2\) $J(E_1)$ 0
2520.c.680400.1 2520.c \(y^2 + (x^2 + 1)y = -75x^6 - 65x^4 - 19x^2 - 2\) $G_{3,3}$ 0
2610.a.2610.1 2610.a \(y^2 + (x^3 + 1)y = 8x^6 + 19x^5 + 39x^4 + 41x^3 + 39x^2 + 19x + 8\) $G_{3,3}$ 0
2640.a.2640.1 2640.a \(y^2 + (x^3 + x)y = -x^6 - 10x^4 - 40x^2 - 55\) $G_{3,3}$ 0
2688.a.172032.1 2688.a \(y^2 + y = -12x^6 - 36x^5 - 61x^4 - 62x^3 - 42x^2 - 17x - 4\) $G_{3,3}$ 0
2730.a.13650.1 2730.a \(y^2 + (x^3 + 1)y = -x^6 - 5x^5 + 3x^4 + 56x^3 - 7x^2 - 195x + 131\) $G_{3,3}$ 0
Next

Download all search results for